2021
DOI: 10.3390/ijms22073520
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol and Its Glycoside Derivatives as Modulators of Etoposide Activity in HL-60 Cells

Abstract: Kaempferol is a polyphenol found in a variety of plants. Kaempferol exerts antitumor properties by affecting proliferation and apoptosis of cancer cells. We investigated whether kaempferol and its glycoside derivatives—kaempferol 3-O-[(6-O-E-caffeoyl)-β-D-glucopyranosyl-(1→2)]-β-D-galactopyranoside-7-O-β-D-glucuropyranoside (P2), kaempferol 3-O-[(6-O-E-p-coumaroyl)-β-D-glucopyranosyl-(1→2)]-β-D-galactopyranoside-7-O-β-D-glucuropyranoside (P5) and kaempferol 3-O-[(6-O-E-feruloyl)-β-D-glucopyranosyl-(1→2)]-β-D-g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…In our previous papers, we analyzed the impact of kaempferol and its glycoside derivatives isolated from Lens culinaris Medik. on HL-60 cells and PBMCs (peripheral blood mononuclear cells) treated with etoposide [28,29]. We demonstrated that kaempferol glycosides reduced the DNA damage induced by etoposide in PBMCs, but they did not have an impact on the DNA damage in HL-60 leukemic cells [28].…”
Section: Introductionmentioning
confidence: 81%
“…In our previous papers, we analyzed the impact of kaempferol and its glycoside derivatives isolated from Lens culinaris Medik. on HL-60 cells and PBMCs (peripheral blood mononuclear cells) treated with etoposide [28,29]. We demonstrated that kaempferol glycosides reduced the DNA damage induced by etoposide in PBMCs, but they did not have an impact on the DNA damage in HL-60 leukemic cells [28].…”
Section: Introductionmentioning
confidence: 81%
“…Moreover, the investigated flavonols at a concentration range of 5–50 µM neither protected UN-SH-SY5Y and RA-SH-SY5Y cells against Dox-evoked damage nor potentiated the Dox cytotoxicity. Kaempferol and several of its glycosides, however, can potentiate the cytotoxic action of the antineoplastic agent etoposide as it was shown recently by Kluska and coworkers in HL-60 cells [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three ATCC (Manassas, VA, USA) human leukemia cell lines were chosen, namely AML (acute promyelocytic HL-60 [ 27 ] and chronic myelogenous K-562 [ 28 ]), and ALL (T-cell acute lymphocytic MOLT-4 [ 23 ]) types. They were cultured with RPMI medium (Gibco; Grand Island, NY, USA) and mixed with 10% FBS and antibiotics (50 U/mL penicillin and 50 μg/mL streptomycin).…”
Section: Methodsmentioning
confidence: 99%